2016
DOI: 10.1186/s12891-016-1064-1
|View full text |Cite
|
Sign up to set email alerts
|

IL17A and IL17F gene polymorphisms in patients with rheumatoid arthritis

Abstract: BackgroundInterleukin-17 plays important role in the pathogenesis of rheumatoid arthritis (RA). The aim of this study was to examine the associations between polymorphisms in the IL17A and IL17F genes and RA.MethodsWe examined 422 RA patients and 337 subjects as a control group. Single nucleotide polymorphism (SNP) in the IL17A (rs2275913) and IL17F (rs763780, rs11465553, rs2397084) genes were genotyped using TaqMan genotyping assays from Life Technologies Genomic.ResultsThere were no significant differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 24 publications
2
43
0
Order By: Relevance
“…Finally, seven studies including 1,409 RA patients and 1,303 controls were eligible for the present study. [13][14][15][16][17][18][19] The flow chart of the literature research and study selection is shown in Figure 1. Among the included studies, all seven investigated the correlation between 7488A/G and RA susceptibility, but only four (containing 1,093 cases and 969 controls) researched 7383A/G and RA risk.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, seven studies including 1,409 RA patients and 1,303 controls were eligible for the present study. [13][14][15][16][17][18][19] The flow chart of the literature research and study selection is shown in Figure 1. Among the included studies, all seven investigated the correlation between 7488A/G and RA susceptibility, but only four (containing 1,093 cases and 969 controls) researched 7383A/G and RA risk.…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, all seven investigated the correlation between 7488A/G and RA susceptibility, but only four (containing 1,093 cases and 969 controls) researched 7383A/G and RA risk. 13,14,16,19 Moreover, in the study of Louahchi et al, 19 only allele data could be extracted. The main characteristics of these studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rheumatoid arthritis (RA) is an autoimmune disease characterized by a chronic in ammatory response that affects various part of the human body. At late stages, RA leads to deformities of the joints and bones causing severe pain [1][2][3][4][5]. Certain factors were hypothesized to be involved in the induction and the development of RA; however, the most acceptable theory for the development of the disease is a multifactorial theory that involve the interaction of environmental and genetic background of patients and render them more susceptible to RA [6].…”
Section: Introductionmentioning
confidence: 99%